RNA-stable isotope probing: from carbon flow within key microbiota to targeted transcriptomes. (October 2016) - Lueders, Tillmann; Dumont, Marc G; Bradford, Lauren; Manefield, Mike
Graphical abstract: Highlights: RNA-SIP allows for a labelling-based detection of process-relevant microbes independent of cellular replication or growth. Recent RNA-SIP based advances in our understanding of carbon flow in complex natural microbiota, of organismic interactions and in environmental biotechnology are summarized. The combination of RNA-SIP and next-generation sequencing is a promising strategy for targeted environmental transcriptomics. Abstract : Stable isotope probing of RNA has enthused researchers right from its first introduction in 2002. The concept of a labelling-based detection of process-targeted microbes independent of cellular replication or growth has allowed for a much more direct handle on functionally relevant microbiota than by labelling of other biomarkers. This has led to a widespread application of the technology, and breakthroughs in our understanding of carbon flow in natural microbiomes, autotrophic and heterotrophic physiologies, microbial food webs, host–microbe interactions and environmental biotechnology. Recent studies detecting labelled mRNA demonstrate that RNA-SIP is not limited to the analysis of rRNA, but is currently developing towards an approach for accessing targeted transcriptomes. In combination with next-generation sequencing and other methodological advances, RNA-SIP will continue to deliver invaluable insights into the functioning of microbial communities.